The semisitting position in pediatric neurosurgery: pearls and pitfalls of a 10-year experience - Teping, Fritz; Linsler, Stefan; Zemlin, Michael; Oertel, Joachim (Journal of Neurosurgery-Pediatrics, 2021)
OBJECTIVE The authors sought to investigate the pearls and pitfalls of using the semisitting position in pediatric neurosurgery, with special focus on related morbidity and surgical practicability. METHODS All pediatric cases at a single institution were evaluated retrospectively. Those patients who underwent procedures in the semisitting position between December 2010 and December 2020 were included in the final analysis. Results were compared with all children who underwent surgery in the prone position for posterior fossa lesions within the same time frame. RESULTS A total of 42 posterior fossa surgeries were performed in 38 children in the semisitting position between December 2010 and December 2020. The mean patient age at the time of surgery was 8.9 years (range 13 months–18 years). The data of 24 surgeries performed in the prone position in 22 children during the same time frame were analyzed in comparison. Three children (7.9%) were diagnosed with a persistent foramen ovale preoperatively. The surgery was completed in all cases. The incidence of venous air embolism (VAE) was 11.9%. There was no VAE-related hemodynamic instability, infarction, or death. Endoscopic techniques were applied safely in 14 cases (33.3%). Postoperative pneumocephalus occurred significantly more frequently in patients who had undergone procedures in the semisitting position (p < 0.05), but without the need for intervention. During 1 surgery (2.4%), the patient experienced a postoperative skull fracture and epidural bleeding due to the skull clamp application. Clinical status of the patients immediately after surgery was improved or stable in 33 of the 42 surgeries (78.6%) performed in the semisitting position. CONCLUSIONS With attentive performance and an experienced surgical team, the semisitting position is a safe option for posterior fossa surgery in the pediatric population. With a comparable complication profile, the semisitting position offers excellent anatomical exposure, which is ideal for the application of endoscopic visualization. Careful skull clamp application and appropriate monitoring are highly recommended.
CRIS-Team Scopus Importer:2023-12-20
Keywords: Pediatric neurosurgery; Posterior fossa; Semisitting position; Sitting position; Surgical technique